Local perspectives of the formalization of knowledge transmission: the Nunamin Illikakvia/learning from the land project, Ulukhaktock, NWT - Stephenson, E; Pearce, T; Cunsolo Willox, A; Ford, J (ArcticNet Inc., 2013)
Across the Canadian Arctic there are concerns that local and traditional knowledge is not being passed on to younger generations. This is attributed to disruptions to traditional education systems including resettlement of communities, residential schooling and displacement, technological changes in transportation and navigation, economic change and timeconstraints of waged employment, environmental change, and reduced interest from youth who occupy a very different cultural space from that of their Elders. However, access to and skills for land-based activities is important for both physical and mental health, and may be especially crucial under conditions of rapid climatic change, as loss of land skills may compromise safe and eff ective hunting and travel. Ensuring that local and traditional knowledge is successfully shared and exchanged with younger generations has become a priority for many Arctic communities. Research and funding institutions also now seek to promote traditional ecological knowledge for priorities such as cultural preservation, health promotion, and adaptive capacity. Under these conditions, more formalized programs to teach/transmit local and traditional knowledge are being initiated across the Canadian Arctic. Such programs range from the purpose-built Piqqusilirvvik Inuit Cultural School in Clyde River, to the Junior Canadian Rangers program funded by the Department of National Defence and the Canadian Forces, to programs created and delivered by community groups. Many programs are also interlinked with and supported by academic research activities. Th is trend raises a number of questions: How does formalization change the knowledge system and social relationships that underpin it? Can formalized programs remain in line with local values for education? Who benefits from this type of program? Can land skills and values be taught this way? How do research and funding agency needs, such as evaluation, scheduling, and priority areas, affect the local implementation and continuity of programs? In association with one such program in Ulukhaktok, NWT, the Nunamin Illihakvia: Learning from the Land project funded by Health Canada, we seek to better understand community members’ perspectives on the formalization of knowledge transmission and answer the above questions. Working closely with Ulukhaktokmiut researchers and interpreters, we employ in-depth key informant interviews with Elders and skills teachers both involved in and outside of the Nunamin Illihakvia, and conduct semi-structured interviews with program participants. Expected contributions of this study include a critical analysis on the impacts of formalization on knowledge systems, key considerations for researchers involved in framing or advancing knowledge transmission and land skills programming, and an avenue for greater inclusion of local voices within the knowledge transmission scholarship.